Relationships between Outcome Expectancies and Non-Suicidal Self-Injury: Moderating Roles of Emotion Regulation Difficulties and Self-Efficacy to Resist Self-Injury - Hird, Kirsty; Hasking, Penelope; Boyes, Mark (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Background: Non-suicidal self-injury (NSSI) is the deliberate damage of one’s own body tissue in the absence of suicidal intent. Research suggests that individuals engage in NSSI as a means of regulating their emotions and that NSSI is associated with emotion regulation difficulties. There is also evidence supporting the role of outcome expectancies and self-efficacy to resist NSSI. However, it is unclear how these factors work together to explain NSSI. Objective: To explore whether the relationships between five NSSI-specific outcome expectancies and NSSI history are moderated by emotion regulation difficulties and self-efficacy to resist NSSI. Method: 1002 participants (Mage = 20.51, 72.5% female, 39.7% lifetime history of NSSI) completed an online survey including measures of NSSI history, outcome expectancies, self-efficacy to resist NSSI, and emotion regulation difficulties. Results: Emotion regulation difficulties were associated with NSSI, as was expecting NSSI to regulate affect. Conversely, expectations of communication and/or pain, as well as self-efficacy to resist NSSI were negatively associated with NSSI. Expectancies also interacted with both difficulties in emotion regulation and self-efficacy to resist NSSI in predicting self-injury. For example, the association between expectations of affect regulation and self-injury was weaker when associated with greater self-efficacy to resist NSSI. Conclusion: These findings provide support for considering NSSI-specific cognitions in concert with emotion regulation when understanding NSSI.Highlights Outcome expectancies can differentiate people based on NSSI history. Emotion regulation difficulties and self-efficacy to resist NSSI moderate the relationships between outcome expectancies and NSSI history. Emotion regulation difficulties and low self-efficacy to resist NSSI work together to predict NSSI history.